KEBIJAKAN PENGHAPUSAN BARANG MILIK DAERAH DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI RIAU TAHUN 2017 - Siti Zahra Habibah; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Regional Property of Riau Province in the framework of carrying out Regional Government annually in quantitative and qualitative manner continues to increase well in the implementation of Government, development and society. Therefore, a coordinated and integrated policy and step is needed regarding the Management of Regional Property with a focus on the elimination of Regional Property by the Riau Provincial Government at the Riau Provincial DPRD Secretariat. However, there are still perceived obstacles, especially in the elimination, because the policy of eliminating Regional Property has not been maximized as evidenced by the Governor's Decree to carry out deletion, consequently the capacity of storage warehouses for goods that have been overloaded due to the deletion process has never been carried out in the Riau Provincial DPRD Secretariat until this. The purpose of this study was to describe the Policy for the Elimination of Regional Property and its obstacles in the Secretariat of the Riau Provincial Regional Representative Council in 2017. This research is a qualitative research. This research was conducted at the Secretariat of the Riau Provincial Regional Representative Council in 2017. The technique used to collect data in this study was (1) Interview and (2) Documentation. The conclusion of this study shows that the policy of the Elimination of Regional Property in the DPRD Secretariat of Riau Province in 2017 has not been maximized because there is no Governor's Certificate related to deletion. Since 2012 the Property Manager of the DPRD Secretariat has implemented the proposed deletion, but the abolition process was constrained in the assessment process. Inhibiting factors of the Regional Property Eradication Policy at the Secretariat of the Riau Provincial Regional Representative Council in 2017 related to George C. Edward III's Theory, namely: (a) Lack of communication of orders and direction, (b) Lack of resources, and (c) Lack of bureaucratic structure carried out between the Secretariat of the Riau Provincial Regional Representative Council, the Office of the Governor of Riau Province and the Office of the Regional Finance and Asset Audit Agency of Riau Province. Keywords: Policy, Elimination, Regional Property